Direct identification of fish species by surface molecular transferring. Issue 12 (9th May 2020) - Shao, Mingke; Bi, Hongyan
Abstract : A surface molecular transferring strategy is the first to be utilized for the direct analysis of fish samples by mass spectrometry, and it promisingly enables fish authentication in a quick, efficient and easy mode. Abstract : With the expansion of the aquatic market and the large quantity of seafood consumption, the issues on safety, traceability and authenticity of seafood are becoming more and more important. Herein, a mass spectrometric method by direct analysis of fish samples was developed for fish authentication. A high-throughput matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI TOF MS) technique was applied to analyze the substances on the fish skin, or the surface molecularly imprinted substances on the surface of muscle tissues using a MALDI-target plate. A multivariate analysis was executed on the obtained mass spectra, and plots of principal component analysis (PCA) for different fish samples were differently clustered in a 95% confidence level. The developed strategy was capable of classifying and identifying fish species. The molecular imprinting method was found with good analytical reproducibility. The strategy enables the distinguishment of fish samples in a quick, efficient and easy mode. It is promising to apply the presently developed strategy for the authentication of seafood and extend the protocol for the detection of other protein food products.